Viscosity of Potassium Fluoride in Mixed Solvent at Different Temperatures - Sahu, H.S.; Mohanty, P.C.; Mohanty, J.R.; Misra, P.K. (Asian Journal of Chemistry, 2016)
Ion-solvent interaction has been inferred from the B coefficient of Jones-Dole equation for potassium fluoride in ethanol, methanol, isopropanol, dioxane, glycol and glycerol + water mixture at 10, 20 and 30% (w/w) within the temperature range 30–40ºC.